Molecular analysis of neurofibromatosis type 1 in Turkish families using polymorphic markers - Oğuzkan, Sibel; Cinbiş, Mine; Ayter, Sükriye; Anlar, Banu; Aysun, Sabiha (The Turkish Journal of Pediatrics, 2003)
Neurofibromatosis type 1 (NF1) is a common autosomal dominant disorder characterized by multiple neurofibromas, café-au-lait spots, and Lisch nodules of iris. The NF1 gene is located on chromosome 17q11.2 and encodes an 11-13 kb mRNA containing 60 exons. The NF1 gene product neurofibromin is a large protein of 2818 amino acids which acts as a negative regulator in the ras signal transduction pathway. The disease has a high mutation rate and a wide range of expression. Because of the size and complexity of the gene, the variety of mutations and the need to identify the specific mutation in each family, indirect diagnosis using linked markers has an important part in genetic counseling. We analyzed 10 Turkish families with a total of 28 affected individuals and 34 non-affected relatives using polymorphic sequences, four intragenic and five flanking markers. Intragenic microsatellite markers were highly informative for all families. As a result, prenatal and presymptomatic diagnoses for familial cases are being made available.